Pengembangan E-Modul Proyek Penguatan Profil Pelajar Pancasila Dengan Tema Gaya Hidup Berkelanjutan - Puspariyani, Aurelia Ratih; Handayani, Dewi; Amir, Hermasyah (Chemistry Education Practice, 2024)
This research is a research and development e-module project to strengthen the profile of Pancasila students with the theme of a sustainable lifestyle. This research was carried out from March to July 2024 at SMA Negeri 1 Bengkulu City, with research subjects namely 31 class XA students. This research aims to determine the level of feasibility of e-modules and student responses to e-modules. This development uses a 4-D development model (define, design, development, and disseminate) which is limited to the development stage. The instruments in this research were interview sheets, student needs questionnaires, validation sheets, and student response questionnaires. From the research results it is known that (1) the feasibility level of the e-module has a very feasible category with a score of 93.8%, (2) the results of the student response test to the e-module received a score of 88.1% with a very good category. The e-module developed is equipped with explanations, images and videos which can be accessed using a smartphone connected to the internet network. Keywords: E-module, Pancasila Student Profile, Sustainable Lifestyle